Venous thromboembolism in radiation therapy cancer patients: Findings from the RIETE registry,. - Jean-Baptiste Guy; Laurent Bertoletti; Nicolas Magné; Chloé Rancoule; Ihloé Rancoule; Isabelle Mahé; Carme Font; Oscar Sanz; José Manuel Martín-Antorán; Federica Pace; Jerónimo Ramón Vela; Manuel Monreal and the RIETE Investigators; et al. (Elsevier, 2017)
Background: Cancer patients are at high risk of venous thromboembolism, particularly during cancer treatment. Conversely to chemotherapy, data on the epidemiology and clinical features of venous thromboembolism during radiation therapy are scarce. There is lack of evidence on the influence of radiation therapy (RT) on outcome in cancer patients with acute venous thromboembolism (VTE). Methods: We used the RIETE (Registro Informatizado de Enfermedad ThromboEmbolica) database to assess the clinical characteristics and outcome of prospectively-collected consecutive patients with cancer-associated thrombosis occurred during the course of radiation therapy for cancer. Death, venous thromboembolism recurrences and major bleeding rates during long-term follow-up according to cancer site and treatment were compared RESULTS: 9284 Patients with active cancer and VTE were enrolled in RIETE: 4605 with pulmonary embolism (PE) and 4679 with deep vein thrombosis (DVT). In all, 1202 (13%) were receiving RT. This last sub-population had a higher rate of PE recurrences and a similar rate of DVT recurrences or major bleeding than those not receiving RT. Patients on RT had a higher rate of cerebral bleeding. Conclusions: In this cohort of cancer patients with VTE, a significant proportion of them received RT before VTE, the latter experienced a higher risk of cerebral bleeding.
Keywords: Anticoagulant therapy; Cancer; Pulmonary embolism; Radiation therapy; Venous thromboembolism